2016
DOI: 10.3892/etm.2016.3279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on extracts from Hericium erinaceus by different polarity reagents to gain higher antioxidant activities

Abstract: Abstract. Hericium erinaceus (H. erinaceus)is a source of exogenous antioxidants that has been traditionally used in China for the prevention and treatment of oxidative stress-associated disease. In the present study, the bioactive compounds of H. erinaceus were extracted with the following eight representative reagents: n-Hexane, xylene, chloroform, anhydrous ether, ethyl acetate, acetone, anhydrous ethanol and distilled water. The in vitro antioxidant activities were also evaluated. All of the extracted comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…HESAE was further extracted with ethanol to obtain compounds with lower polarity and the phytochemical analysis revealed the presence of adenosine and herierin III. Hydro-alcoholic extractions have been recommended for the recovering of biologically active compounds of mushrooms including phenolic compounds and flavonoids [ 54 , 55 ]. Further, Jiang et al [ 54 ] showed that anhydrous ethanol appeared to be the most efficient solvent in the extraction of high-polarity components of H. erinaceus contributing to high antioxidant activity as measured by reducing power and free radical scavenging assays.…”
Section: Discussionmentioning
confidence: 99%
“…HESAE was further extracted with ethanol to obtain compounds with lower polarity and the phytochemical analysis revealed the presence of adenosine and herierin III. Hydro-alcoholic extractions have been recommended for the recovering of biologically active compounds of mushrooms including phenolic compounds and flavonoids [ 54 , 55 ]. Further, Jiang et al [ 54 ] showed that anhydrous ethanol appeared to be the most efficient solvent in the extraction of high-polarity components of H. erinaceus contributing to high antioxidant activity as measured by reducing power and free radical scavenging assays.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that a purified compound may not necessary possess antioxidant function compared to its extract counterpart. Ethanol and water extracts of H. erinaceus showed more potent reducing power and free radical scavenging activities compared to low polarity solvents, indicating that antioxidant compounds are often concentrated in more polar solvents (Jiang et al, 2016). HESAE was prepared by high polarity aqueous extraction of fresh fruiting bodies to ensure total extractable phenolic, flavonoid and antioxidant contents (Mau et al, 2002;Wong et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They are of interest because of their medicinal attributes [ 13 ]. A mushroom, Hericium erinaceus , was reported to possess a wide range of therapeutic features such as antioxidant [ 14 ], anti-tumorigenic [ 15 ] and endoplasmic reticulum stress modulatory activities [ 16 ], and hericenones and erinacines found from this fungus are promising candidates for dementia therapies [ 17 ]. Ganoderma lucidum has been used as a general preventive medicine for thousands of years in eastern Asia.…”
Section: Introductionmentioning
confidence: 99%